Mikrotik VPN Shielding E-Link Health Reports: Strengthening Data Security at Madiun Health Office - Gumelar, Bintang Agung; Putra, Guruh Darma Setiya; Amadi, Dwi Nor (Journal of Information Systems and Informatics, 2023)
Advances in Information and Communication Technology have led to revolutionary changes in computer networking, especially in Indonesia, which has witnessed significant technological growth over the last four years. Despite this progress, inter-agency data exchange, particularly in governmental organizations, remains vulnerable to security risks. This study focuses on enhancing the security measures for the Electronic Health Information Report (E-Link) system at Madiun District Health Office by implementing a Virtual Private Network (VPN) using MikroTik. A multi-method approach, comprising direct observation, interviews, and literature review, was adopted for this investigation. The findings confirm that the utilization of Point-to-Point Tunneling Protocol (PPTP) via MikroTik substantially elevates the security and governs controlled access to the E-Link application. Therefore, the implementation of a VPN not only fortifies the security but also improves the accessibility of health data systems.
Keywords: VPN, Virtual Private Network, Network Security